Educação, formação humana e tecnologia : diálogos com o homem unidimensional de Marcuse - Verdin, Alessandra Martins dos Santos (2015)
This work falls within the framework of theoretical research in the field of the philosophical foundations of critical education. The problem of research concerns the challenges that the concepts of technology and culture, present in the Herbert Marcuse‟s reflections, could provide to the critical theory of education today. The reflection revolves around the formation processes from their relationship with technology, specifically with Internet. Starts on Herbert Marcuse‟s philosophical foundation, on culture and technology concepts in the book One-Dimensional Man and in the articles About the culture’s affirmative character and Comments to a redefinition on the culture’s concept. The hypothesis is that the concepts developed by the author – in dialogue with socially constituted phenomena as well as emerging – go against the grain of the logic of hegemonic technical-instrumental rationality. Takes as its starting point the literature review whose results reveals the relevance and interest by this theme in the educational field and also notes the paucity of jobs from Marcuse‟s critical philosophy, both national as international sources. By the critical analysis of accessed works is possible to infer that technology, mediated by Internet, can also cause the use to impoverish and reduce ways to perceive and signify events, relationships, projections and possibilities, and can change the character of subjectivity through appropriation processes of damaged evidence of memory and culture. Combined with advertising and self-promotion techniques, these elements corroborates to configure and applicate the one-dimensional cognitive design inside people, comfortably surrendered to the society‟s logic that produces it. The potential use of technological tools free of technical-instrumental rationality design that overlaps the sensitive and loving facet of human life – typical of late capitalism of advanced industrial societies –, can reverse the movement of intellectual technological and political organization, of conquest and manipulation of negative thinking, the unhappy consciousness, freedoms, needs, desires, ways of managing free time, projection living standards which together curtail movements to social change.